The Concordance of Three Diagnostic Test for Malassezia folliculitis using Potassium Hydroxide 20% + Blue-Black Parker Ink, May Grunwald Giemsa, and Potassium Hydroxide 10% + Chicago Sky Blue - Dyatiara Devy Rahadiyanti; Evy Ervianti; Damayanti Damayanti; Dwi Murtiastutik; Sawitri Sawitri; Afif Nurul Hidayati (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Malassezia folliculitis is a pilosebaceous follicular infection disease caused by Malassezia species. There are many misdiagnosed Malassezia folliculitis cases, causing the maladministration of therapy. A routine diagnostic test performed for Malassezia folliculitis cases is the identification of fungal elements (spore) with a microscope using potassium hydroxide, but it has several weaknesses. Purpose: To evaluate the suitability of Malassezia folliculitis diagnostic test using Potassium Hydroxide 20% + Blue-Black Parker Ink, May Grunwald Giemsa, and Potassium Hydroxide 10% + Chicago Sky Blue. Methods: Analytic observational study conducted in the Dermatomycology Division of Dermatology and Venereology outpatient clinic, Dr. Soetomo General Hospital Surabaya. The samples were thirty patients with clinical features of Malassezia folliculitis. The research material was obtained from the body as many as three pieces of papulomoluscoid lesion extracted. The material obtained was then divided into three glass objects for Potassium Hydroxide 20% + Blue-Black Parker Ink, May Grunwald Giemsa, and Potassium Hydroxide 10% + Chicago Sky Blue staining. Result: The identification of spores using Potassium Hydroxide 20% + Blue-Black Parker Ink was 90%, May Grunwald Giemsa was 90%, and Potassium Hydroxide 10% + Chicago Sky Blue was 93% with a value of κ=0.348 and p=0.051. The diagnostic values of May Grunwald Giemsa and Potassium Hydroxide 10% + Chicago Sky Blue were 96.6% sensitivity, 33.3% specificity, 92.9% Positive Predictive Value, and 50 % Negative Predictive Value. Conclusions: There was no significant concordance between May Grunwald Giemsa and Potassium Hydroxide 10% + Chicago Sky Blue with Potassium Hydroxide 20% + Blue-Black Parker Ink in establishing the diagnosis of Malassezia folliculitis. Potassium Hydroxide 20% + Blue-Black Parker Ink is still needed as a routine examination in cases with clinical features of Malassezia folliculitis.